Generating disaggregated poverty maps: an application to Viet Nam - Minot, Nicholas (International Food Policy Research Institute, 1998)
Geographic targeting is often recommended as a way to improve the impact of social spending and infrastructure investments on rural poverty. Previous research shows that such targeting is not very accurate unless the geographic units are small. Household surveys, however, rarely allow the estimation of poverty rates for more than 5-10 regions in a country. This study develops a method for generating disaggregated poverty maps and applies the method to Viet Nam. First, the relationship between rural poverty and 25 household indicators is estimated using household survey data. Then, census data on those same indicators are used to estimate the poverty rates for each of the 543 rural districts in Viet Nam. The results indicate that poverty is concentrated in the north and in districts furthest from the coast and cities.